Amikor (kollektív) bűn volt magyarnak lenni a Felvidéken. A kassai kormányprogram és a Beneš-dekrétumok ismertetése és hatása a Szlovákiai Református Keresztyén Egyház életére az 1945–48 közötti években - SOMOGYI, Alfréd (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2017)
When it Was a Sin to Be Hungarian in Slovakia. After the second world war, the plan was to create a nation-state from the renewed Czechoslovakia. The head of the state, Edvard Beneš’s intention was, to make the Germans and Hungarians, living in the country, disappear. He blamed these two nations, and the German and Hungarian minorities living in Czechoslovakia for the collapse of the country in 1938. The creation of a nation-state was supported by the Great Powers. In 1945, the Red Army liberated the former territories of Czech-oslovakia and in the absence of a central government, Edward Beneš started to rule by issuing presidential decrees. He issued 143 decrees, amongst them those pro-claiming the collective war crime of Germans and Hungarians, loss of their citizen-ship, confiscation of their properties, and it sent them to forced labour. This started their expulsion from their homeland. Hungarians were deported to Czech territory, then expelled to Hungary, finally forcefully resettled to Hungary in exchange for Slovaks living in Hungary. The plan was to "shift" 400.000 Hungarians to Hungary. In the end, 90.000 people were deported, out of them 50.000 of reformed religion. This paper deals with the effects of the deportations, resettlements from the re-formed church’s point of view.